2008
DOI: 10.4049/jimmunol.181.11.7778
|View full text |Cite
|
Sign up to set email alerts
|

Egr2 Is Required for Bcl-2 Induction during Positive Selection

Abstract: The repertoire of TCR specificities is established by a selection process in the thymus, during which precursor survival and maturation is dictated by the nature of the TCR signals. The differences in signals that determine whether precursors will survive and mature or be induced to die remain poorly understood. Among the molecular effectors involved in executing the differentiation process initiated by TCR-ligand interactions is a family of Zn-finger transcription factors termed early growth response genes (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 41 publications
7
48
2
Order By: Relevance
“…We also bred Egr2 f/f CD4Cre mice with Tg mice expressing either the OTII TCR, in which thymocytes are selected into the CD4 lineage, or the F5 TCR, in which thymocytes are selected into the CD8 lineage, both on RAG-deficient backgrounds to preclude rearrangement and expression of endogenous TCR. In line with other workers [26], we found that on an …”
Section: Egr2 Levels Do Not Affect Lineage Commitmentsupporting
confidence: 81%
See 1 more Smart Citation
“…We also bred Egr2 f/f CD4Cre mice with Tg mice expressing either the OTII TCR, in which thymocytes are selected into the CD4 lineage, or the F5 TCR, in which thymocytes are selected into the CD8 lineage, both on RAG-deficient backgrounds to preclude rearrangement and expression of endogenous TCR. In line with other workers [26], we found that on an …”
Section: Egr2 Levels Do Not Affect Lineage Commitmentsupporting
confidence: 81%
“…Recently, analysis of mice in which Egr2 was deleted in DN thymocytes has shown that it is not required for negative selection, but that positive selection of both CD4 and CD8 lineages is impaired in the absence of Egr2. This defect is at least partially due to increased apoptosis as it is rescued by overexpression of the survival factor Bcl-2 [26]; however, the mechanism by which Egr2 might be regulating survival has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Egr2 is dependent on ERK and calcineurin signaling; the endogenous repressor Nab2 inhibits Egr2 in neurons and T cells (30, 36, 60 -62). Induction of anti-apoptotic protein Bcl-2 is regulated by Egr2 during positive selection and survival of thymocytes (27,29). Egr2 polymorphisms have been associated with altered immune response in SLE and neuropathies related to survival of inflammatory cells (63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of Bcl-2 has been shown to be regulated by Egr2 during positive selection and survival of thymocytes (27,29). Egr proteins comprise a family of transcriptional regulators (Egr1-4) that modulate gene expression involved in the growth, differentiation, and survival of a variety FIGURE 2.…”
Section: Trem-1 Prolongsmentioning
confidence: 99%
See 1 more Smart Citation